The gold diplomacy in Greco-Persian relations - Igor Vladimirovich Vostrikov, Eduard Valerievich Rung, Elena Aleksandrovna Venidiktova, (Opción, 2019)
In article, the authors focus on goals, methods and means of the Persian Gold diplomacy towards the Greeks, and collect all relevant data from Greek sources, which deal with different aspects of Persian diplomatic dealings with the Greeks via comparative qualitative re-search methods. In result, the Persian Gold Diplomacy was a sequence of the Achaemenid gift-given tradition. It did not reflect some peculi-arities of the Persian relations with the Greek world. In conclusion, coercive Earth-and-Water Diplomacy and Gold Diplomacy were the implementation of a stick and carrot approach by the Achaemenid in their relations with the foreign countries and rulers